Proteomic profile of sex-sorted bull sperm evaluated by SWATH-MS analysis - Scott, Caroline [UNESP]; de Souza, Fabiana F. [UNESP]; Aristizabal, Viviana H.V. [UNESP]; Hethrington, Louise; Krisp, Christoph; Molloy, Mark; Baker, Mark A.; Dell'Aqua, José Antônio [UNESP] (Elsevier, 2018)
The identification of distinct proteins present on the membrane of spermatozoa with X and Y chromosomes allows the development of immuno-sexing techniques. The aim of this study, therefore, was to use mass spectrometry to analyze the protein profile of sperm previously categorized using flow cytometry into X or Y-bearing semen pools. Sex-sorted sperm samples (n = 6 X and n = 6 Y) were used. Proteins were extracted and analyzed by mass spectrometry using data independent acquisition (DIA). The data were searched against taxonomy Bos taurus in the Swiss Prot database. In total, 459 protein groups were identified. Of these, eight proteins were in differential abundances between the X- and Y-bearing sperm population. Among the major proteinsdetected, EF-hand domain-containing protein 1, a protein involved in embryonic development, is more abundant in Y-bearing spermatozoa. In addition, proteins FUN14, domain-containing protein 2, NADH dehydrogenase [ubiquinone] iron-sulfur protein 7 mitochondrial, cytochrome C oxidase subunit 2, acetyl -CoA carboxylase type beta were more abundant in X-bearing sperm. In conclusion, there were differences in abundance of proteins between X- and Y-bearing bull spermatozoa. This fact, may contribute to future studies related to sperm physiology and possibility development of immuno-sexing techniques.
Keywords: Bovine; Immuno-sexing; Proteomics; Sex-sorted-sperm